2010
DOI: 10.1103/physrevlett.105.263004
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Coupled Cluster Theory

Abstract: We describe a stochastic coupled cluster theory which represents excitation amplitudes as discrete excitors in the space of excitation amplitudes. Reexpressing the coupled cluster (CC) equations as the dynamics of excitors in this space, we show that a simple set of rules suffices to evolve a distribution of excitors to sample the CC solution and correctly evaluate the CC energy. These rules are not truncation specific and this method can calculate CC solutions to an arbitrary level of truncation. We present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
145
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(147 citation statements)
references
References 13 publications
2
145
0
Order By: Relevance
“…This means population control bias is likely to be more of a problem for calculations which require smaller timesteps, such as strongly correlated systems, or calculations using coupled cluster Monte Carlo. 11 We also note that converging FCIQMC calculations to µE h accuracy has previously been attempted. 32 In this regime, the population control bias could potentially become similar in magnitude to the stochastic error.…”
Section: Discussionmentioning
confidence: 99%
“…This means population control bias is likely to be more of a problem for calculations which require smaller timesteps, such as strongly correlated systems, or calculations using coupled cluster Monte Carlo. 11 We also note that converging FCIQMC calculations to µE h accuracy has previously been attempted. 32 In this regime, the population control bias could potentially become similar in magnitude to the stochastic error.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that CCMC calculations have a higher plateau than configuration interaction quantum Monte Carlo (CIQMC) calculations at the same truncation level. 39 It is likely that this is because the excips have to explore a larger effective Hilbert space than the psips in the equivalent CIQMC simulation, so more excips are required to make the annihilation rate high enough to suppress the in-phase signal.…”
Section: Discussionmentioning
confidence: 99%
“…In the CCMC and full configuration interaction quantum Monte Carlo (FCIQMC) approaches, a population of particles in Fock space represents the wavefunction and evolves according to simple rules of spawning, death, and annihilation. 83,87 For a CC Ansatz, unit particles may represent nonunit contributions to CC amplitudes by letting the intermediate normalisation condition vary with the population on the reference determi-…”
mentioning
confidence: 99%